Percutaneous Pharmaco-Mechanical Thrombectomy of Acute Symptomatic Superior Mesenteric Vein Thrombosis - Rabuffi, Paolo (Cardiovasc Intervent Radiol, 2019)
PURPOSE: To evaluate the safety and the efficacy of percutaneous pharmaco-mechanical thrombectomy (PPMT) of acute superior mesenteric vein (SMV) thrombosis. METHODS: A database of patients treated between 2011 and 2018 with acute venous mesenteric ischemia (VMI) was reviewed. VMI was diagnosed in the presence of SMV thrombosis and CT evidence of jejunal thickening. All patients presented with mild to moderate peritonism, which allowed surgery to be postponed. Initial treatment consisted of heparinization. PPMT was indicated in case of worsening abdominal pain despite anticoagulation and was performed via a transjugular or transhepatic approach, using a rotational aspiration thrombectomy catheter, followed by transcatheter thrombolysis. Clinical success was defined as symptoms resolution. Technical success was defined as patency of > 50% of SMV at venography and resolution of jejunal thickening. Patients were discharged on lifelong oral anticoagulation (INR 2.5–3.5). Follow-ups were performed using CT and color Doppler ultrasound. RESULTS: Population consisted of eight males, aged 37–81 (mean 56.5 years). Causes for thrombosis were investigated. Urokinase infusion time ranged from 48 to 72 h (3,840,000–5,760,000 IU). Clinical and technical success was obtained in all cases. One patient experienced bleeding from the superior epigastric artery and was treated with embolization. One patient died of multi-organ failure after 35 days, despite resolution of SMV thrombosis. In no case was surgery required after PPMT; mean hospitalization was 14.1 days (9–24). Mean follow-up of remaining seven patients was 37.7 months (12–84 months). CONCLUSION: PPMT of acute SMV thrombosis seems safe and effective, with an 87.5% long-term survival rate and a 12.5% major complication rate.